Design and Development of an Educational Game for Learning Ecosystem Harmony Using the MDLC Method - Syafni Amaliah; Aidil Primasetya Armin (Jurnal Teknologi Riset Terapan, 2025)
Purpose: This study aimed to design and develop an educational game as an interactive learning medium to improve fifth-grade elementary school students’ understanding of ecosystem harmony, particularly food chains and food webs, which are often difficult to understand through conventional learning methods. Methodology/approach: This study was conducted at SD Negeri Sukorejo, Turi District, Lamongan Regency, involving 14 fifth-grade students. The educational game, HAMORA (Harmoni Ekosistem Rantai Makanan), was developed using the Multimedia Development Life Cycle (MDLC) method, which includes concept, design, material collection, assembly, testing, and distribution stages. Unity was used as the development engine, and the visual assets were designed using Canva. Data were collected through interviews and observation of classrooms. The evaluation consisted of Black Box testing, compatibility testing on various Android devices, usability testing using the System Usability Scale (SUS), and learning effectiveness testing through pre- and post-tests. Results/findings: The results show that the application runs smoothly on multiple Android devices, and all features function properly. The usability evaluation achieved an average SUS score of 77.14, indicating an acceptable level with a good interpretation. The learning effectiveness analysis revealed an improvement in students’ understanding, with N-Gain values categorized as moderate. Conclusions: The HAMORA educational game was successfully developed as an interactive learning medium that enhances student engagement and understanding of ecosystem harmony. Limitations: This study was limited to one elementary school and focused only on food chain and food web materials. Contributions: This study provides a practical reference for implementing game-based learning in elementary education.